1 CHARACTERISTICS OF PATIENTS RECEIVING PHARMACEUTICAL SAMPLES AND ASSOCIATION BETWEEN SAMPLE RECEIPT AND OUT-OF-POCKET PRESCRIPTION COSTS. (1st March 2007) - Alexander, G.; Zhang, J.; Basu, A.
Abstract : Background: Pharmaceutical samples are widely used for promotion and marketing, yet little is known about who receives samples or how their use is associated with patient's prescription costs. Objective: To examine the characteristics of patients receiving samples and to describe the association between sample receipt and prescription costs. Design, Setting, and Participants: We divided the 2002-2003 Medical Expenditure Panel Survey, a nationally representative, panel-design longitudinal study, into baseline and analysis periods. We conducted logistic and generalized linear regression analysis of 5, 709 individuals in the analysis period who did not receive any samples during the baseline period. Measurements: (1) Sample receipt and (2) prescription expenditures Results: A total of 781 (14%) individuals received at least one sample during the analysis period. On multivariate analyses, sample receipt was greater among those who were younger and those not on Medicaid. In generalized linear regressions controlling for demographic characteristics and health care use, the 180-day out-of-pocket prescription expenditures were 178 (standard error [SE] 3.9) for those never receiving samples. Among those receiving samples, the corresponding out-of-pocket expenditures were 166 (SE 8.9) for periods before sample receipt, 244 (SE 9.2) for periods during sample receipt, and 212 (SE 12.4) for periods following sample receipt. Results were similar when total prescription costs were examined. Limitations: Sample use was based on self-report, the analysis period was limited to 12 months, and the associations observed may not be causal. Conclusions: Individuals receiving samples have higher prescription expenditures than their counterparts. This finding, which may be from sample-induced demand for prescriptions, as well as greater illness among sample recipients, suggest that sample recipients may be disproportionately burdened by prescription costs even after sample receipt.